Metabolic Correction Therapy as Adjuvant Treatment for Breast Cancer Patients: A Case Report - Navarrete, Marilís; Centeno, Jomaris; J Gonzalez, Michael; J. Berdiel, Miguel (Journal of Breast Cancer Survival, 2018)
Breast cancer is the most common cancer in women worldwide. In the United States, is the second leading cause of cancer deaths in women. In Puerto Rico between 2008 and 2012, breast cancer was the most diagnosed type of cancer and the leading cause of cancer deaths among women. This is a case of 54 years old female diagnosed with stage IV right breast carcinoma. The patient complaints were weakness and a right breast ulcer. She started a metabolic correction therapy, which consisted of high intravenous vitamin C infusions, a nutritional supplementation plan, and Paleolithic diet. During treatment, both Glycohemoglobin and Carcinoembryonic Antigen levels decreased significantly, the right breast ulcer decreased in size, and the patient’s quality of life improved. Over the years, vitamin C studies have demonstrated a cytotoxic action against malignant cells. Based on the results from this case, we advocate continue studying possible adjuvant treatments for cancer patients, involving IV infusions of vitamin C and metabolic correction plans.
Keywords: Breast Cancer; Metabolic Correction Therapy; Intravenous Vitamin C; Adjuvant Treatment; Nutritional Supplementation; Case Report